Very-Early Onset Chronic Active Colitis with Heterozygous Variants in LRBA1 and CARD11, a Case of "Immune TOR-Opathies". (4th March 2023) - He, Mai; Wong, Amanda; Sutton, Kimberly; Gondim, Mercia Jeanne Bezerra; Samson, Charles
Abstract: Background: A small subset of cases of inflammatory bowel disease (IBD) occurs as a result of single gene defects, and typically occurs in young or very young pediatric patients, referred to as "monogenic very-early onset IBD (VEO-IBD)". The gene variants leading to monogenic VEO-IBD are often associated with primary immunodeficiency syndromes. Case report: A six year-old girl presented to our gastroenterology clinic with LRBA deficiency with a heterozygous mutation at c.1399 A > G, p Met467Val, histopathologic chronic active colitis without granulomas and clinical chronic colitis. Her gastrointestinal symptoms began at age 5 with bloody diarrhea, abdominal pain and weight loss. Whole exome sequencing revealed a CARD11 heterozygous de novo mutation (c.220 + 1G > A). She was in clinical remission on only abatacept. Discussion: We present a case of monogenic VEO-IBD associated with two heterozygous variants in LRBA1 and CARD11, both considered as key players in the newly proposed "immune TOR-opathies".